Characterization and potential of plant growth-promoting rhizobacteria on rice seedling growth and the effect on Xanthomonas oryzae pv. oryzae (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rahma H, Nurbailis, Kristina N. 2019. Characterization and potential of plant growth-promoting rhizobacteria on rice seedling growth and the effect on Xanthomonas oryzae pv. oryzae. Biodiversitas 20: 3654-3661. Xanthomonas oryzae pv. oryzae (Xoo), a major limiting factor in rice production, and the use of resistant Xoo varieties have failed to control the bacterial pathogens as well as increased yield. It is due to the diversity in pathotypes, caused by environmental factors, the nature of resistant variety used, and gene mutation. The aims of this study were to select rhizobacterial strains with the potential of suppressing Xoo growth and promoting the growth of rice seedlings. This experiment was conducted in a completely randomized design (CRD) using seven rhizobacterial isolates selected through a dual culture test, with four replications. There were four isolates that potential in inhibiting the growth of Xoo, namely KJKB5.4, LMTSA5.4, Bacillus cereus AJ34, and Alcaligenes faecalis AJ14, with inhibition diameters greater than 11.50 mm. Rhizobacterial supernatant of 4 potential isolates has a zone of inhibition ranging from 12.25 to 24.00 mm. Four potential isolates were also able to solubilize phosphate, produce indole acetic acid (IAA) growth hormone, and siderophore, as well as enhance the growth of rice seedlings. Based on the nucleic acid sequencing of LMTSA5.4, KJKB5.4, and RK12 isolates were identified as Stenotrophomonas malthopilia strain LMG 958 (99.13%) accession NR 119220.1, Stenotrophomonas pavanii strain LMG 25348 (95.84%) accession NR 118008.1 and Ochrobactrum ciceri strain ca-34 (92.91%) accession NR115819.1.
Keywords: Antagonists, biological agents, indole acetic acid, phosphate solubilization, siderophore